Óleos essenciais e seus componentes bioativos para uso frente a doenças negligenciadas e arbovirose: Uma revisão - Luna, Emanuela Coutinho (2019)
This dissertation is a bibliographic review that deals with neglected diseases (diseases with higher incidence in underdeveloped countries, affecting mainly the lower income population) and the pharmacological potential that essential oils have on these diseases. Of the 17 neglected diseases described by the World Health Organization, four were selected for this study: dengue, Chagas disease, leishmaniasis and sleeping sickness. To compose the literature database, a systematic search was performed in several databases: PubMed, Web of Science, Medline, Scopus, Science Direct, Scielo, Cochrane Library, Coffee Platform and Lilacs. The search was limited to articles published in the last 10 years without language restriction using various keyword combinations: “essential oils”, “neglected diseases”, “terpenes”, “phenylpropanoids”, “leishmaniasis”, American trypanosomiasis”, “sleeping sickness”, “African trypanosomiasis”, “arbovirus” and “dengue”. This literature review gave rise to an article that was published in the journal Oxidative Medicine and Cellular Longevity and is entitled Active Essential Oils and their components in use against Neglected Diseases and Arboviruses. After compiling the bibliography we observe that there is a wide range of essential oils, their fractions or their isolated components with prominent activity on the neglected diseases analyzed. This study could be used as a basis for selecting some plants for further study of their pharmacological properties, or for selecting more promising molecules that can serve as a basis for structural modification of new bioactive compounds with enhanced biological properties to enhance the quality of their research for any of these diseases.